ANALISIS KEBUTUHAN MODAL KERJA PADA RUMAH MAKAN BINTANG LIMA DI SAMARINDA - Yundi Permadi Hakim; Santi Mulyani (Jurnal Ekonomi dan Manajemen, 2017)
Working Capital Needs Analysis at Star Restaurant in Samarinda. In its operational activity, sometimes the excess or insufficiency of working capital hence the usage of the fund less effective and efficient until now the owner of Bintang Restaurant in Samarinda not yet know the actual condition and have not yet analyzed the use of working capital requirement whether need the addition of working capital or not, more in the future. The formulation of the problem in this research is: "Do You Still Need to Increase Working Capital Needs at Star Restaurant in Samarinda? The purpose of this research are: 1) to know and analyze the amount of working capital needed, 2) to know and analyze the speed of working capital turnover every year or each perimeter, 3) to know and analyze the factors that influence the small amount of capital work at Bintang Restaurant in Samarinda. The analytical tool used by using comparative analysis is by comparing the speed of working capital turnover of 2014 and 2015 and to set the target or sales volume forecast of 2016 until 2018 is done projection or forecasting with linear regression trend method which result is: Y = 313.502.500 + 43.642.750 (X). From the analysis results obtained sales volume forecast for the year 2016 amounting to Rp 400.788.000,00 and in 2017 amounting to Rp 444,430,750.00 and for the year 2018 amounting to Rp 488,073,500,00, always experienced a significant increase. The need of working capital required at Bintang restaurant in Samarinda 2016 based on working capital available Rp 361.467.000,00 while the result of analysis amounting to Rp 318.085.714.00 so no need to increase working capital requirement because it has excess of Rp 43.381.285,715 with rotational speed the operation of working capital for 2016 is 1.26 times and in 2017 the working capital requirement is Rp 501,245,000.00 while based on the analysis result of Rp 266,126,197,605, so there is no need for additional working capital requirement because it has excess of Rp 235.118.802,3950 with the velocity of 1.67 times, so thus, the hypothesis in the research put forward the author is correct and acceptable